Pengaruh Penggunaan Media Puzzle Gambar Terhadap Minat Dan Hasil Belajar Ipa-Biologi Pada Pokok Bahasan Struktur Dan Fungsi Jaringan Tumbuhan Siswa Kelas Viii Smp Muhammadiyah 1 Surakarta Semester Genap Tahun Ajaran 2015/2016 - Rahayu, Sri, Dr. Sofyan Anif, M.Si (2016)
The aim of this research paper is to get to know the influence of the use of puzzle pictures media toward the interests and the learning outcomes in Biology of students in VIII SMP. The type of this research is to describe the quantitative approach done through true experiments. The population of research of all students VIII SMP Muhammadiyah 1 Surakarta second semester year 2015/2016 with the sample of 51 students with through random sampling. The techniques of collecting data are observation, documentation, questionnaire, and test. The data analysis is using multivariate analysis of MANOVA. Success in this research can be known by the average posttest results in class VIII E (experiment) reaches 54,73 and class VIII D (control) to 47,69 , after MANOVA test can be concluded that there is no effect of the puzzle pictures to student interest, but there is the influence of the puzzle pictures to student learning outcomes.